ANALYSIS OF MULTILITERACY-BASED INQUIRY LEARNING VS. GUIDED DISCOVERY: IMPACT ON INDONESIAN HISTORY LEARNING OUTCOMES - Djakariah, Djakariah; Akbar, Jakub Saddam (JURNAL EDUSCIENCE, 2025)
Purpose- This research aims to determine the differences in Indonesian history learning outcomes between students taught with the multiliteracy-based inquiry and guided discovery learning models and the influence of prior knowledge on these learning outcomes.Methodology-This research uses an experimental design with a quantitative approach. The research sample consisted of 50 high school students divided into two groups: the group taught using the Multiliteracy-Based Inquiry model, and the group taught using the Guided Discovery model. The instruments used were initial knowledge tests and Indonesian History learning outcomes tests. Data were analyzed using a two-way analysis of variance.Findings- The research results show significant differences in Indonesian history learning outcomes between the two learning model groups, with the group using the multiliteracy-based inquiry model showing higher results. In addition, there are significant differences between students with high and low prior knowledge, with students with high initial knowledge having better learning outcomes. However, no significant interaction effect was found between the learning model and previous knowledge of Indonesian History learning outcomes.Significance-The conclusion of this research shows that the Multiliteracy Inquiry learning model is more effective in improving student learning outcomes than the Guided Discovery learning model. This research implies that this learning model can be implemented to enhance Indonesian history learning in high school. This research can be helpful for educators and researchers who are interested in developing more effective learning methods.Keywords: Keywords: Learning models; inquiry; multiliteracy; Guided discovery; Prior knowledge